THE EFFECTS OF SEXUAL TRAUMA TOWARDS VIOLENCE IN THE NOVEL VENGEANCE IS MINE, ALL OTHERS PAY CASH BY EKA KURNIAWAN - Salniyah; Latumeten, Anna Anganita Theresia (Prologue: Journal on Language and Literature, 2025)
This study examines the effects of sexual trauma on violent behavior in the novel Vengeance Is Mine All Others Pay Cash by Eka Kurniawan. There are two objectives of this study: to find out the forms of sexual trauma found in the novel, and to describe how sexual trauma effects violence. The study employs two theories: Herman's theory of sexual trauma and Fromm's theory of violence. The methodology used is qualitative research with primary data presented in descriptive form. Data were collected from the novel, while secondary data and other relevant sources were gathered through literature review. The results of the study indicate that the researcher found four forms of sexual trauma: childhood sexual abuse, sexual assault, sexual harassment, and sex trafficking. To examine the effects of sexual trauma on violence, the researcher utilized Fromm's theory, which distinguishes between benign aggression and malignant aggression. The researcher found that the most dominant type of sexual trauma was sexual harassment, which significantly impacts violent behavior. Specifically, sexual harassment often leads to violent behavior categorized as both malignant aggression. In conclusion, sexual trauma has a strong effect on the manifestation of violence in the forms of malignant in the novel.